Beating the Odds! Build theory from emerging markets phenomenon and the emergence of case study research—A “Test-Tube” typology - Kotapati Srinivasa Reddy; Tahir Nisar (Cogent Business & Management, 2015)
The extant social sciences and management theoretical concepts and empirical literature have mostly determined based on western (developed) economies institutional context. In the recent past, a number of researchers have argued that the western theories are inadequate to study the emerging markets phenomenon and described the problems relating to data collection, data analysis, and theory development. I also (experience) confirm that major problems are relating to the research data collection, especially primary data (interview and survey methods). With this in mind, I develop a new case study research design, that is, “Test-Tube” typology, to build theory from emerging markets behavior as well as to add new knowledge to the mass of disciplines, particularly social sciences, medicine, travel, tourism and hospitality, sports, management, and information systems, and engineering. I design a typology that consists of eleven steps: case development, case selection, relatedness and pattern matching, case analysis, cross-case analysis, theoretical constructs, pre-testing and development, adjusting theoretical constructs, theory testing, building theory and testable propositions, and suggesting strategic swap model. Further, I suggest a set of few guidelines on how to measure the research quality and how to strengthen the research rigor in case study settings.
Keywords: 650